Martin Luther : selections from his writings - Luther, Martin, 1483-1546.; Dillenberger, John. (Garden City, N.Y. : Anchor Books, 1961)
The development of Martin Luther's thought was both a symptom and moving force in the transformation of the Middle Ages into the modern world. Geographical discovery, an emerging scientific tradition, and a climate of social change had splintered the unity of medieval Christian culture, and these changes provided the background for Luther's theological challenge. His new apprehension of Scripture and fresh understanding of man's relation to God demanded a break with the Church as then.
Constituted and released the powerful impulses that carried the Reformation. Luther's vigorous, colorful language still retains the excitement it had for thousands of his contemporaries. In this volume, Dr. Dillenberger has made a representative selection from Luther's extensive writings, and has also provided the reader with a lucid introduction to his thought.
Preface to the complete edition of Luther's Latin writings, 1545 -- Selected Biblical prefaces -- The freedom of a Christian, 1520 -- Two kinds of righteousness, 1519 -- A commentary on St. Paul's Epstile to the Galatians, 1531 (selections) -- The bondage of the will, 1525 (selections) -- Sermons on the Catechism, 1528 (selected) -- Sermon in Castle Pleissenburg, Leipzig, 1539 -- The pagan servitude of the church, 1520 -- Secular authority : to what extent it should be obeyed, 1523 -- An appeal to the ruling class of German nationality as to the amelioration of the state of Christendom, 1520 -- The Ninety-five Theses, 1517 -- Theses for the Heidelberg Disputation, 1518.
Includes bibliographical references (pages 504-506).
Includes indexes.
Keywords: Theology -- Early works to 1800.; Theology -- History -- 16th century; Lutheran Church; Lutheran Church; Theology; 1500-1599; Early works; History